The Fundamental of Social Housing for M40 Group : A Review - Masitah, Zulkepli; UmaDevi, Raman; Ahmad Ariffian, Bujang; Lim, Boon Keong; Azizah, Ismail; Wilson Rangga, Anthony Jiram (2024)
Providing adequate, suitable and affordable housing in meeting the housing need of household is one of the objectives of the country’s socioeconomic development. However, housing issues within the M40 group in Malaysia remain a major challenge, they do not qualify for low-cost housing and cannot afford even medium-cost housing. Whereas, developers are concentrating on developing a housing project for T20 group. In 2019, Malaysian National Housing Department has revealed that the idea of social housing in Malaysia is still at the early stage. Therefore, a clearer concept needs to be addressed in order to resolve the urban poverty and housing need for M40 Group. Thus, this paper attempts to review the social housing concept and fundamental criteria which will facilitate government’s initiation of housing access policy for M40 group. This study is expected to provide a thorough understanding and knowledge about social housing concept and fundamental criteria for M40 group.